Twin-twin transfusion syndrome (TTTS) - Huamán Guerrero, Moisés (2015)
Objectives: To review twin-twin transfusion syndrome (TTTS) comparative results by techniques used in regards to diagnosis, treatment, survival and complications, as well as current management of this complication in Peru. Methods: Articles published in specialized bibliographic sources were revised, and experience in Peru and Chile on management of this syndrome was analyzed. Results: TTTS is an uncommon complication of monochorionic twin pregnancy with major repercussion on the health of both fetuses. Treatment of choice of severe cases (Quintero I-IV) is fetoscopic laser photocoagulation of superficial and deep anastomoses at 18-26 weeks of pregnancy. About 140 cases per year occur in Peru and implementation of this technique is necessary. Conclusions: Elective treatment of severe cases of TTTS is fetoscopic laser photocoagulation of superficial and deep anastomoses between 18-26 weeks of gestation. This technique should be implemented in Peru.